Differences between Male and Female College Students in Dynamic Stability Change through Measuring Lower Extremity Muscle Fatigue - Hae sung Lee; Sung-Sik Ko; Keun-Ok An (Asian Society of Kinesiology, 2019)
OBJECTIVES The purpose of this study was to compare and analyze differences by gender, changes in dynamic stability due to lower extremity muscle fatigue. METHODS A total of 47 college-age students participated in the experiment. Subjects consisted of 29 males and 19 females. A muscle fatigue squat protocol with Smith machine and Y-balance Test was conducted and measurements were taken before and after the onset of fatigue. RESULTS There were statistically significant differences before and after fatigue in anterior right leg (p<.001), anterior left leg (p<.001), posteromedial right leg (p=.011), posteromedial left leg (p=.010), pesterolateral left leg (p=.014), total score right leg (p<.001) and total score left leg (p<.001), the only exception being posterolateral right leg (p=.057). The difference between male and female groups decreased in a statistically significant manner on posteromedial left leg (p=.045) and posterolateral right leg (p=.031). The effects of interaction between measurement periods did not represent statistically significant differences in all categories. CONCLUSIONS The result of this study represented a decrease in total score of Y-balance Test before and after the application of muscle fatigue. There were no gender differences in the dynamic stability of male and female subjects due to muscle fatigue.